Edukasi Anti Penyalahgunaan Obat Kepada Siswa SD Di Kota Palu Melalui Media Kartu Kuartet: Education of Anti-drug Abuse for Elementary School Students in Palu Citythrough Quartet Card Media - Hannan, Hannan; Wikaningtyas, Pratiwi; Adnyana, I Ketut (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
Cases of illegal drugs and drug abuse in the elementary school community in Indonesia is increasingly massive and alarming. An innovation to protect elementary school students from that situation is through the colaboration of academics from Bandung Institute of Technology with FDA in Palu in the form education of anti-drug abuse for elementary school students through quartet card media. The aim of the study was to determine the effect of the education on anti-drug abuse knowledge in fifth grade students in Palu City. The research method used pre-experimental design with the design of one group pretest-posttest on three elementary schools which were representatives of three ranks namely; good, quite good and not good based on the results of the Smart-Accurate Quiz FDA in Palu for elementary school level in 2017. The sampling technique used purposive sampling. Observation of knowledge of elementary students using questionnaires that have been tested for validity and reliability had been carried out. The pretest and posttest were conducted before and after education. The comparison of pretest and posttest data in each elementary school was analyzed using paired T test whereas for all elementary school data analyzed using the Wilcoxon test with hypotheses. There was an influence of anti-drug abuse education through quartet card media on anti-drug abuse knowledge in fifth grade students in Palu City. The results showed that there was an influence of education on anti-drug abuse knowledge in fifth grade students from elementary school representatives â€œgood and quite good rankingâ€ with p values of 0.005 and p â‰¤ 0.001, while in elementary schools representatives â€œnot good rankingâ€, the education did not influence their knowledge with a p value of 0.149. Analysis of the Wilcoxon test in all elementary schools showed a p value p â‰¤ 0,001, which meant that education had an influence on the knowledge of fifth grade students in elementary schools in Palu City.